Near Is My Shirt, But Nearer Is My Skin: Ideology or Self-Interest as Determinants of Public Opinion on Fiscal Policy Issues - Gerhard Schwarz; Hans Pitlik; Bernd Brandl; Barbara Bechter (Verein für Socialpolitik, 2010)
Several empirical studies derive that personal positions with respect to policy measures are dominated by ideology instead of narrow self-interest. In the present field study we carried out a telephone survey with 1.003 respondents all over Austria. Instead of only measuring self-interest indirectly, we requested respondents to assess directly whether they expect to be affected by policy measures. Our results indicate that such a subjectively measured narrow self-interest explains attitudes towards economic policies at least as good as ideological conviction. In some cases, however, ideology appears to determine whether people feel affected by a proposed policy measure.
Keywords: D72; D83; D84; 330; public opinion; sociotropic voting; ideology; self-interest; telephone surveys